Alcohol and illicit drugs in drivers involved in road traffic crashes in the Milan area. A comparison with normal traffic reveals the possible inadequacy of current cut-off limits. (January 2018) - Ferrari, Davide; Manca, Monica; Banfi, Giuseppe; Locatelli, Massimo
Highlights: Alcohol abuse in northern Italy is widespread between different generations. Drugs abuse in northern Italy is more common in younger generation. The 0.5 mg/ml cut-off limits for alcohol blood concentration is appropriate. The 2 and 10 ng/ml cut-off limits for THC and cocaine respectively might be inappropriate. Abstract: Background: Driving under the influence of alcohol and/or illicit drugs in Italy is regulated by the articles 186 and 187 of the National Street Code. Epidemiological studies on drivers involved in road traffic crashes (RTC) provide useful information about the use/abuse of these substances in the general population. Comparison with case control studies may reveal important information like the cut-off limits adequacy. Methods: Data from 1587 blood tests for alcohol and 1258 blood tests for illicit drugs on drivers involved in RTC around Milan between 2012 and 2016, were analyzed and compared with a published random survey (DRUID) from the European Community. Results: Our data from RTC-involved drivers show that alcohol abuse is not age-related whereas illicit drugs are more common in young people. Cannabinoids are frequent among younger drivers (median age 27) whereas cocaine is more often detected in adults (median age 34). The calculated odds ratio after comparison with the DRUID survey shows that a blood alcohol concentration below the legal limit does not represent a risk factor in having a car accident whereas concentrations of cocaine and cannabinoids within the legal limits are associated with being involved in a car accident. Conclusions: Despite authority efforts, the abuse of alcohol and illicit drugs is still common in young drivers. We suspect that the cut-off limits for cannabinoids and cocaine and/or the pre-analytical procedures for these substances are inadequate. We suggest a better standardization of the procedure by shortening the time interval between the request for investigation and blood collection and propose the adoption of more stringent cut-off limits.